Subjective mapping of indoor plants based on leaf shape measurements to select suitable plants for indoor landscapes - Tokuhiro, Kenro; Sugimoto, Hiroki; Ikeuchi, Akinori; Tsujie, Takeshi; Wada, Eriko; Muramatsu, Masayoshi; Ohto, Chikara (Building and environment, 2025)
•A subjective plant map of 40 indoor plants based on plant impressions was prepared.•The physical shapes of leaves were measured that could represent a subjective map.•Both experts and people reported relaxation and liveliness on seeing plants.•Plants with small leaves induced a sense of relaxation.•Leaf shape classification may assist in selecting plants for indoor landscapes. Interest in incorporating plants in indoor landscapes is now increasing given the psychological benefits of indoor plants. Although many plant species are used for indoor greenery, little is known about the types of plants that promote well-being and suit different room applications. Herein, indoor plants were categorized based on the shape of their leaves. Experts in interior plant design evaluated 40 indoor plant species based on their visual and psychological impressions. Using these subjective impressions, the experts created a two-dimensional map to categorize and compare the plants. The plants were then classified into four groups: relaxation, concentration, liveliness, and surprise. Experts compared the impressions of whole plants and their leaves, and we found that leaf shape significantly affected the overall plant impression. Thus, we measured the physical shape of the leaves and found that three measurements (length, width, and roundness) selected for multiple regression analysis could represent the plant positions in the subjective map. A photographic questionnaire results confirmed that relaxation scores for plants with small leaves were consistent between experts and web survey participants. In addition, we identified a possible relationship between relaxation effects and the fractal dimensions of leaves, highlighting the influence of leaf shape on psychological responses. These findings suggest that leaf shape classification is a novel and simple approach for selecting suitable indoor plants, thereby enhancing indoor landscape design for well-being.